2011
DOI: 10.1166/jnn.2011.4716
|View full text |Cite
|
Sign up to set email alerts
|

Tough Yttria-Stabilized Zirconia Ceramic by Low-Temperature Spark Plasma Sintering of Long-Term Stored Nanopowders

Abstract: Weakly agglomerated 1.75 and 3 mol% yttria stabilized zirconia nanopowders were used in this study after six years of storage in vacuum-processed plastic containers. The proper storage conditions of the Y-TZP nanopowders avoided the hard agglomeration. Untreated and bead-milled nanopowders were used to obtain dense ceramics by slip casting and subsequent low-temperature sintering. Fully dense nanostructured 1.75Y-TZP and 3Y-YZP ceramics with and without doping of 1 wt% Al2O3 were produced by an optimized spark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It decreases regularly from C1 to C6 upon the increase in the carbon content ( Table 2). The SENB fracture toughness of C0 (10.3 MPa.m 1/2 - Table 2) is the highest among those reported for such a ceramic with an average grain size below 200 nm [9,[48][49][50], even when the measurements are made by the SEVNB method [15]. The fracture toughness of both C0.5 and C1 is still relatively high (about 7 MPa.m 1/2 ).…”
Section: Mechanical Propertiesmentioning
confidence: 85%
“…It decreases regularly from C1 to C6 upon the increase in the carbon content ( Table 2). The SENB fracture toughness of C0 (10.3 MPa.m 1/2 - Table 2) is the highest among those reported for such a ceramic with an average grain size below 200 nm [9,[48][49][50], even when the measurements are made by the SEVNB method [15]. The fracture toughness of both C0.5 and C1 is still relatively high (about 7 MPa.m 1/2 ).…”
Section: Mechanical Propertiesmentioning
confidence: 85%
“…It is observed that densification values for the SPSed samples lie in the range~93 to 96 pct, which is slightly lower than the range of values found in literature. [2,[41][42][43] It is to be noted that multi-stage SPS has been employed in the current work with uniaxial pressure of 30 MPa and maximum sintering temperature of 1523 K (1250°C). In contrast, higher temperature or uniaxial pressure has been utilized by other researchers while processing zirconia ceramics, hence accounting for the greater densification (98 to 100 pct) reported in their work.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21] In contrast, comparatively quick processing techniques (5-10 minutes as compared to 40 hours) such as hotpressing and field-assisted (FAST) sintering such as the spark plasma sintering (SPS), microwave sintering (MWS) are usually used for producing dense fine-grained YSZ. [22][23][24][25][26] At the present time the SPS and MWS are considered as the most effective methods of obtaining bulk fine-grained YSZ, because of high heating rates, achieved by electrical heating via graphite die or volumetric dielectric heating. [27][28][29][30] In case of SPS the benefit of the applied external field (i.e., pulsed electric current) is not restricted to Joule heating, other non-thermal benefits are operative, such as current enhanced mass transport, and reactivity.…”
Section: Introductionmentioning
confidence: 99%